GENEALOGI DALAM RANGKA PENCIPTAAN SERAT DARMASARANA KARYA R. NG. RANGGAWARSITA - Anung Tedjowirawan (Humaniora, 2006)
The goal of the writing of Serat Darmasarana by R.Ng. Ranggawarsita is the reception of Âdiparwa and continuation of the story of Mosalaparwa, Prasthanikaparwa, and Swargarohanaparwa. By writing Serat Darmasarana and texts in the Pustakaraja Madya R.Ng. Ranggawarsita intends to place Pengging as a myth, as the central government in Java, after the fall of Kediri. Further, R.Ng. Ranggawarsita also wants to place the Gods and Pandawa as the ancestors of Mataram Kings.